Determination of polycyclic aromatic hydrocarbons in human blood samples using solid phase extraction and gas chromatography mass spectrometry- a review - Al-Battawi, Samer; Ho, Yu Bin; Latif, Mohd Talib; How, Vivien; Karuppiah, Thilakavathy (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous pollutants with toxic effects and adverse health impacts on general population. Several methods of extraction had been applied to extract PAHs from human blood samples such as solid phase extraction (SPE). The SPE represents one of the most common techniques for extraction and clean-up procedures as it needs low quantity of solvents with less manual efforts. Similarly, various analytical instruments like gas chromatography coupled to mass spectrometry (GC-MS) was used to measure the PAHs levels. Gas chromatography is a simple, fast, and very efficient method for solvents and small organic molecules. This review provides an overview of the measured concentrations of PAHs in human blood samples through the application of SPE and GC-MS during the last ten years. While these studies used various solvents, their application of SPE method and GC-MS revealed rewarding results about the determination of PAHs levels in the human samples.